Home Visit Sebagai Metode Pembelajaran Anak Usia Dini Pada Masa COVID-19 - Maila D.H. Rahiem; Amelia Novi (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
The aim of this study was to investigate and assess parents' and teachers' views of the home-visiting program as a method of early childhood education during the COVID-19 outbreak. Exploratory qualitative research employed as methods of inquiry. Twelve resource persons were interviewed (3 teachers and 9 parents). The data revealed, parents and teachers perceive that using home visits has a number of benefits and drawbacks. The benefits are as follows: 1) more effective than online; 2) make learning materials easy for children to understand; 3) pique children's interest and excitement for learning; and 4) eliminate the need for parents to assist their children with their tasks. Meanwhile, the downsides include the following: 1) it was inconvenient for parents because they were needed to entertain teachers and other children; 2) some pupils couldn't study because home visits were far away from their homes.; 3) additional media and learning activities preparation; 4) additional time and energy was wasted; and 5) the risk of exposure to COVID-19 was increased. The researchers recommend that additional study be conducted with a larger and more diverse sample size in order to obtain a more complete picture of this issue.